Creating Innovators : The Making of Young People Who Will Change the World - Wagner, Tony; Video material produced by Robert A. Compton (New York Scribner, 2012)
From the founder of Harvard's Change Leadership Group comes a provocative look at why innovation is today's most essential real-world skill and what young people need to become innovators
Include Index and notes
Keywords: Technological innovations -- Educational change -- Education, Secondary--Aims and objectives